The effectiveness of Powerpoint-iSpring integrated multiple chemical representation learning media on acid-base materials to improve students learning outcomes for Senior High School - Seiski Afrita Riska; Guspatni Guspatni (Jurnal Pijar Mipa, 2022)
We have previously produced a PowerPoint-iSpring Integrated Learning Media Multiple Chemical Representations on Acid-Base Materials. It is valid and practical but has not been tested for its effectiveness on student learning outcomes in Senior High School. The research is experimental with a quasi-experimental design with a Non-equivalent Control Group Design. The research population is all class XI Senior High School students for the 2021/2022 academic years. Purposive sampling was used as a sampling technique with homogeneous sampling criteria. The classes selected as samples were class XI MIPA 1 as the experimental class and class XI MIPA 2 as the control class. The instruments used were questionnaires and student learning outcomes tests in the form of 20 multiple choice questions. The N-Gain and hypothesis testing were carried out for data analysis with an independent sample t-test. Based on the data analysis, the N-Gain of the experimental class was higher than the control class with the medium category. PowerPoint-iSpring Integrated Learning Media with Multiple Chemical Representations on Acid-Base Materials is Effective for Improving Learning Outcomes of Class XI Senior High School Students.